Dietary vitamin D intake and risk of type 2 diabetes in the European Prospective Investigation into Cancer and Nutrition: the EPIC-InterAct study. - Abbas, S; Linseisen, J; Rohrmann, S; Beulens, J; Buijsse, B; Amiano, P; Ardanaz, E; Balkau, B; Boeing, H; Clavel-Chapelon, F; Fagherazzi, G; Franks, P; et al. (2014)
BACKGROUND/OBJECTIVES: Prospective cohort studies have indicated that serum vitamin D levels are inversely related to risk of type 2 diabetes. However, such studies cannot determine the source of vitamin D. Therefore, we examined the association of dietary vitamin D intake with incident type 2 diabetes within the European Prospective Investigation into Cancer and Nutrition (EPIC)-InterAct study in a heterogeneous European population including eight countries with large geographical variation. SUBJECTS/METHODS: Using a case-cohort design, 11,245 incident cases of type 2 diabetes and a representative subcohort (N=15,798) were included in the analyses. Hazard ratios (HR) and 95% confidence intervals (CIs) for type 2 diabetes were calculated using a Prentice-weighted Cox regression adjusted for potential confounders. Twenty-four-hour diet-recall data from a subsample (N=2347) were used to calibrate habitual intake data derived from dietary questionnaires. RESULTS: Median follow-up time was 10.8 years. Dietary vitamin D intake was not significantly associated with the risk of type 2 diabetes. HR and 95% CIs for the highest compared to the lowest quintile of uncalibrated vitamin D intake was 1.09 (0.97-1.22) (Ptrend=0.17). No associations were observed in a sex-specific analysis. The overall pooled effect (HR (95% CI)) using the continuous calibrated variable was 1.00 (0.97-1.03) per increase of 1 μg/day dietary vitamin D. CONCLUSIONS: This observational study does not support an association between higher dietary vitamin D intake and type 2 diabetes incidence. This result has to be interpreted in light of the limited contribution of dietary vitamin D on the overall vitamin D status of a person.